Do conto para os quadrinhos: a retextualização de O alienista - Faccini, Ana Sandra Gonçalves (2016)
This research aims to analyze the comic book version of The Alienist by Machado de Assis, produced as a graphic novel by Fabio Moon and Gabriel Bá. The aim is to investigate the retextualization process undertaken by the authors, seeking, in comparison with the source text, whether new meaning effects were built. The analysis is based on the text and meaning production notions presented by theorists such as Bakhtin (2003), Cavalcante (2013), Marcuschi (2008, 2012) and Koch (2003) and in studies by Dell'Isola about retextualization of written genres. In order to help the comic books reading considering the specificities of their language, works from scholars such as Ramos (2012) and Eisner (1999, 2013) are also evoked. The results of this research reveals, among other things, that the authors of the comic book version of The alienist delete sections and reverse the order of descriptions of the original text, not to the detriment of the sense of work of Machado de Assis, which is maintained, but for the sake of rhythm and visual cohesion, which are necessary in a comic book narrative. This study aims to contribute to the language studies that seek to understand not only the dynamics of retextualization, but also the process of meaning production in verbal-visual text.